PENGARUH PENGGUNAAN GULA MERAH DALAM AIR MINUM TERHADAP PRODUKSI TERNAK BURUNG PUYUH - Lily Joris; Shirley Fredriksz (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
The purpose of this research isthe use of brown sugar in the research is done in order to fix the composition of the nutrition due to the difference of nutrition in the feed and the one required by the quails. This research is done in Ambon for the period of one month that were carried in January until February 2020. The components that used in this research are: 75 Quails with 5 months of age that are divided into 3 flocks, Eggs Producing Chicken Feed Par L, and Brown Sugar.The variables that are measured in this research are: feed consumption, water consumption, number of produced eggs, and the weight of the eggs. The design that is used for this research is a Completely Randomized Design. The result of this research in regards to adding brown sugar in quails drinking water shows that: the treatment without adding brown sugar in the water (Control P0) did not shows any real difference with adding 1% of brown sugar to the water (P1) and adding 2% of brown sugar to the water (P2). The adding of 1% of brown sugar to the water (P1) shows a significant difference with adding 2% of brown sugar to the water (P2). Furthermore, water consumption, eggs production, and the weight of produced eggs does not show any difference between all of the tested treatments.